INTERACTIVE TEXTBOOK AS A TOOL OF MODERN DIGITAL EDUCATION (Innovative professional education, 2025)
The article examines the role of interactive textbooks in the context of the digital transformation of education. The advantages of using interactive educational materials are identified, such as personalization of learning, increasing student interest, and accessibility of knowledge. Special attention is paid to the historical aspects of the emergence of interactive textbooks – from the first experiments in creating animated images to modern innovations, such as artificial intelligence, virtual reality, and adaptive learning platforms. The article also analyzes the challenges associated with the implementation of digital textbooks and offers recommendations for their effective use in the educational process. The challenges associated with the implementation of digital textbooks are also highlighted, in particular, technical limitations, the need for teacher training, and the issue of digital equality.
Keywords: digital environment, quality of training, electronic educational resource, methods of data collection